Pathophysiological aspects of proteases - Chakraborti, Sajal ; Dhalla, Naranjan S. (Springer, 2020)
Protease mediated viral infection -- Role of proteases in cancer pathology especially in breast cancer, as well as role of proteases as posible targets for drug development for cancer -- The multifunctional post-prolinedipeptidyl peptidase, DPP9, in EGF signaling, immunity and cancer biology -- Translating the knowledge of functional dynamics towards designing inhibitors of BACE1, a key aspartate protease in Alzheimer's disease -- Cysteine Dependent Aspartate Specific Proteases in Coronary Artery Disease -- Matrix metalloproteases: Potential role in Type 2 Diabetic Nephropathy -- Matrix-metalloproteinases in Breast Carcinoma, Immunohistology and Prognosis